The Illuminated Garden—The Visitation in the Book of Hours of Juana Enriquez (BPR, II/2104) - Ferri, Aida (Religions, 2024)
This article examines the unique depiction of the Visitation in the Book of Hours of Juana Enriquez, housed in the Biblioteca del Palacio Real de Madrid and also known as the Book of Hours of Isabella the Catholic. While the Visitation is a common theme in other Books of Hours, this manuscript’s rendition stands out for its inclusion of visual elements not found in other works by the same illuminator. Through a detailed iconographic analysis, the article emphasizes the significance of the Visitation scene, exploring its visual components and their implications for understanding the spiritual and cultural context of the era. The study aims to highlight the Visitation miniature as a prime example of imagery crafted to serve the inner devotion of its first owner, Juana Enriquez. Ultimately, this research offers a deeper appreciation of the Book of Hours of Juana Enriquez as a product of its time, designed for meditation and contemplation.